Polymer Fuel Cell Based on Polybenzimidazole Membrane: A Review. Issue 5 (24th March 2019) - Kalathil, Ajmal; Raghavan, Ajith; Kandasubramanian, Balasubramanian
ABSTRACT: Recently, conventional fuel cells are being replaced by Polymer Electrolyte Membrane Fuel Cells (PEMFC) due to improved conversion efficiency, eco-friendliness, silent operation, and flexibility. In PEMFC, Polybenzimidazole (PBI) membranes are widely used due to their properties like mechanical & chemical stability, ignition resistance, high proton conductivity, moisture regainability, improved power density, and high temperature feasibility. Considering, above properties, PBI based PEMFC's find applications in engineering sectors like Automobiles, Space, Power back up systems etc. The present review gives state-of the-art & progress of PBI based PEMFC's, their fabrication via nano-materials, along with brief description of other fuel cell technologies. GRAPHICAL ABSTRACT: